Revision rates of trapeziometacarpal total joint arthroplasty in relation to occupational hand force requirements. (November 2021) - Kirkeby, Lone; Frost, Poul; Svendsen, Susanne W.; Hansen, Torben B.
The purpose was to determine revision rates after trapeziometacarpal total joint arthroplasty in working age patients, hypothesizing that higher occupational hand force requirements lead to higher revision rates. We conducted a follow-up study of patients operated 2003–2015. Self-reported job titles at the time of primary surgery were linked with a job exposure matrix to estimate occupational hand force requirements. Time until revision was analysed using Cox regression. The study comprised 222 patients aged 39–65 years (mean 55, SD 6), including 133 patients in the labour market. The median follow-up period was 5 years (interquartile range 4–7) and the overall revision rate was 5/100 person-years. For high versus low occupational hand force requirements, the hazard ratio was 1.5 (95% confidence interval 0.5–4.4). For patients outside the labour market, the hazard ratio was 2.3 (0.9–5.6). Our results did not indicate large effects of high occupational hand force requirements on revision rates. Level of evidence: IV